Effect of variety and processing methods (holding period and drying method) on quality of cassava flour (Kokonte) in the Hohoe Municipality of the Volta region of Ghana - Quintson, Philip Attah-Kumah (2016)
A thesis submitted to The School of Research And Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of a Master of Philosophy in Postharvest Technology.